2010
DOI: 10.1103/physreva.81.042108
|View full text |Cite
|
Sign up to set email alerts
|

Exactly solvable relativistic model with the anomalous interaction

Abstract: A special class of Dirac-Pauli equations with time-like vector potentials of an external field is investigated.\ud An exactly solvable relativistic model describing the anomalous interaction of a neutral Dirac fermion with a\ud cylindrically symmetric external electromagnetic field is presented. The related external field is a superposition\ud of the electric field generated by a charged infinite filament and the magnetic field generated by a straight line\ud current. In the nonrelativistic approximation the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
114
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 23 publications
3
114
0
Order By: Relevance
“…In fact the number of exactly solvable models with matrix superpotentials some of which have the clear physical significance is much more extended. Among them there are also the relativistic models discussed in [12] and many others. We plane to present such models in the following publications.…”
Section: Discussionmentioning
confidence: 99%
“…In fact the number of exactly solvable models with matrix superpotentials some of which have the clear physical significance is much more extended. Among them there are also the relativistic models discussed in [12] and many others. We plane to present such models in the following publications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the quantum discord has attracted much interest in quantum information theory [5][6][7][8][9] such as its relation with the complete positivity [10] and local broadcasting of the state [11]. Furthermore, both Markovian and non-Markovian dynamics of quantum discord have been analyzed not only in theory but also in experiments [12][13][14][15][16]. Whether the quantum discord can be more robust against decoherence [12,13] than entanglement or not [17] is still an open problem [17].…”
mentioning
confidence: 99%
“…Furthermore, both Markovian and non-Markovian dynamics of quantum discord have been analyzed not only in theory but also in experiments [12][13][14][15][16]. Whether the quantum discord can be more robust against decoherence [12,13] than entanglement or not [17] is still an open problem [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In bipartite system, discord [1,2] is first introduced to quantify quantum correlation, which is defined as the difference between two quantum analogues of the classical mutual information. It has been shown that almost all quantum states have nonvanishing discord [3]. Based on this, Ref.…”
Section: Introductionmentioning
confidence: 91%